ASSESSMENT OF GLUCOSE AND LIPID DYSREGULATION IN ACUTE STROKE AND ITS IMPACT ON PATIENT OUTCOMES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute Stroke is a major cause of mortality and long-term disability worldwide. Metabolic abnormalities such as hyperglycemia and dyslipidemia significantly contribute to stroke pathogenesis, severity, and clinical outcomes. Early identification of glucose and lipid disturbances may improve patient management and reduce complications. The present study aimed to evaluate glucose and lipid abnormalities among patients presenting with acute stroke. Methodology: This hospital-based observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from June 2025 to March 2026. A total of 150 acute stroke patients were included in the study. Demographic and clinical details were recorded. Biochemical investigations including random blood glucose, HbA1c, and lipid profile were performed within 72 hours of admission. Brain CT scans were used to classify stroke types. Statistical analysis was performed using SPSS version 26.0. Results: The mean age of patients was 63 years, with males constituting 55% of the study population. Ischemic stroke accounted for 78% of cases. Glycemic abnormalities included known diabetes (23.3%), undiagnosed diabetes (13.3%), and stress hyperglycemia (13.3%). Elevated LDL-C (56.7%) and low HDL-C (50%) were the most common lipid abnormalities observed. Conclusion: Metabolic abnormalities, particularly hyperglycemia and dyslipidemia, were highly prevalent among acute stroke patients. Early metabolic evaluation and appropriate management may improve clinical outcomes and reduce recurrent cerebrovascular events.